2018
DOI: 10.1089/lap.2018.0002
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy for Morbid Obesity at a Veterans Affairs Medical Center

Abstract: LSG is a safe and effective tool for morbid obesity with clinical and serological improvements for individuals who are unable to lose weight with medical management alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…For the right-predominant type, the trocar beneath the right costal margin was utilized to retract the liver to expose the surgical field. The trocar between the observation trocar and the trocar beneath the right costal margin was used for gastrectomy and subsequent suturing 22 , 56 , 75 . The trocar beneath the left costal margin was used to drag the gastric wall to assist the application of the stapler.…”
Section: Discussionmentioning
confidence: 99%
“…For the right-predominant type, the trocar beneath the right costal margin was utilized to retract the liver to expose the surgical field. The trocar between the observation trocar and the trocar beneath the right costal margin was used for gastrectomy and subsequent suturing 22 , 56 , 75 . The trocar beneath the left costal margin was used to drag the gastric wall to assist the application of the stapler.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (87%) described an observational, retrospective cohort study design (Tables 1-2). Most studies assessed weight outcomes to evaluate weight management programs (41%) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25); the remaining studies evaluated postbariatric surgery weight changes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Sample sizes ranged from 40 (29) to 4,990,424 (36), with most studies (62%) including more than 1,000 patients.…”
Section: Literature Review Samplementioning
confidence: 99%
“…Two additional studies (5%) in this group reported using a Veterans Integrated Services Network database with unclear linkage to the national CDW (22,46). Other studies (44%) described using a facility EHR or related systems (Veterans Health Information Systems and Technology Architecture or Computerized Patient Record System) (11,(13)(14)(15)(24)(25)(26)(28)(29)(30)(31)(32)(33)(34)(35)47,48). The remaining studies were not specific about source or how data were extracted, listing MOVE!…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Характерною ознакою хворих, включених у дослідження, була наявність декількох супутніх захворювань з переважанням патології серцево-судинної системи, яку виявлено у 135 (65,8%) хворих, порушення ліпідного та вуглеводного обміну -у 161 (78,5%) та 135 (65,8%) пацієнтів відповідно, системи травлення -у 130 (63,4%), органів дихання у 63 (30,7%) хворих без статистично значущої різниці за частотою у групах дослідження, що відповідає даним, отриманим у ході досліджень інших авторів [9]. Метаболічний синдром було діагностовано у 135 (65,8%) хворих, включених в дослідження: у 70 (66,6%) хворих основної групи та у 65 (65%) пацієнтів групи порівняння (χ 2 =0,06, p=0,8).…”
Section: результати обговоренняunclassified